2012
DOI: 10.1016/j.dnarep.2011.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The kinetochore protein Bub1 participates in the DNA damage response

Abstract: The DNA damage response (DDR) and the spindle assembly checkpoint (SAC) are two critical mechanisms by which mammalian cells maintain genome stability. There is a growing body of evidence that DDR elements and SAC components crosstalk. Here we report that Bub1 (Budding Uninhibited by Benzimidazoles 1), one of the critical kinetochore proteins essential for SAC, is required for optimal DDRs. We found that knocking-down Bub1 resulted in prolonged H2AX foci and comet tail formation as well as hypersensitivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 36 publications
5
54
0
Order By: Relevance
“…Consistent with the critical roles of the SAC and DDR pathway proteins in checkpoint activation (21), our data indicate that phosphorylation of both Rad53 and ␥-H2A is continuously altered in bub mutants in response to HO-induced DNA damage, whereas these DSB signatures are rapidly diminished in wild-type cells. This suggests DSB repair and resumption of the cell cycle are much quicker in wild-type cells than in the bub mutants, which display these signatures for much longer periods.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Consistent with the critical roles of the SAC and DDR pathway proteins in checkpoint activation (21), our data indicate that phosphorylation of both Rad53 and ␥-H2A is continuously altered in bub mutants in response to HO-induced DNA damage, whereas these DSB signatures are rapidly diminished in wild-type cells. This suggests DSB repair and resumption of the cell cycle are much quicker in wild-type cells than in the bub mutants, which display these signatures for much longer periods.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, the ability of these Bub proteins to interchangeably stimulate the Rad9 and Rad53 DNA damage checkpoint kinases suggests that the Bub pathways provide robust and redundant protection against spindle damage (20) and also implies a likely role for these proteins in response to mitotic DSBs. In fact, recent observations in mammalian cells have indicated that Bub1 functions in the DDR signaling pathway (21), but its role in supporting NHEJ efficiency remains unclear.…”
mentioning
confidence: 99%
“…The observed 1.4-fold increase of meiotic metaphases with cH2AX focus signals (possibly marking unrepaired or not completely repaired DSBs) might explain the ,1.6-fold increase in meiotic metaphase apoptosis in Ku70 2/2 stage XII tubules noted by TUNEL staining. A cross talk between the DNA damage response and the spindle assembly checkpoint has been noted previously (Choi and Lee, 2008;Maringele and Lydall, 2002;Yang et al, 2012) and might be instrumental for this situation.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA damage response and the spindle assembly checkpoint are two critical mechanisms by which mammalian cells maintain genome stability, and there is a growing body of evidence of a cross-talk between these two checkpoint, Indeed, a number of DNA damage responsive elements, including ATM, Chk1, Chk2, and Brca1, have been reported to play a role in spindle checkpoint activation (6,17,32,33). In addition, several proteins involved in SAC such as Bub1 and Mad2 have been shown to play an important role in G 2 /M checkpoint (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several proteins involved in SAC such as Bub1 and Mad2 have been shown to play an important role in G 2 /M checkpoint (33)(34)(35)(36). In particular, Chk1 kinase has been found to sustain activation of SAC in response to DNA damage (36).…”
Section: Discussionmentioning
confidence: 99%